Development of a mathematical model for the prediction of chip formation instability and its verification by fuzzy logic with genetic algorithm - Ullah Patwari, Mohammed Anayet; Amin, A. K. M. Nurul; Istihyaq , M.H.; Faris, Waleed Fekry (inderscience publisher, 2010)
Chip morphology and segmentation play a predominant role in determining machinability and chatter during the machining of different materials. At lower cutting speeds the chip is often discontinuous, while it becomes serrated as the cutting speeds are increased. It has been identified that the chip formation process has a discrete nature, associated with the periodic shearing process of the chip during machining of different materials. Apart from the primary serrated teeth, a typical instability of periodic nature, in the form of secondary saw/serrated teeth, which appear at the free edge of the chip, has been identified. Mechanism of formation of these teeth has been studied and the frequency of their formation has been determined. In this paper, a new analytical technique is proposed to predict the frequency of chip formation instability as a function of cutting parameters. In this technique, a mathematical model has been developed between the cutting parameters and the instability frequency of the chip serration based on response surface methodology and the model is verified by fuzzy logic with genetic algorithm.